Study and Modeling DNA-Preconcentration Microfluidic Device - Nguyen, Viet-Bac; Pham, Van-Sang (Old Journal, 2020)
In this study, to enhance diagnostic efficiency, we focus on the effect of ion concentration polarization (ICP), an electroosmotic (EO) flow, electrophoretic (EP) velocity, and the selective membrane length upon the DNA preconcentration. The study is conducted using the direct simulation of the ions and DNA transport in the electrokinetic system. The transport process is governed by the system of Poisson-Nernst-Planck-Navier-Stokes nonlinear equations. Obtained results show the preconcentrating DNA ability in microfluidic devices, simultaneously point out the implication of the length of the microchannel and selective membranes on DNA plug position. Rely on these results, we proposed an experiment model to increase the efficiency of the DNA preconcentration.